Adobe Photoshop unmasked : the art and science of selections, layers, and paths - French, Nigel (Adobe Press, 2006)
As the feature list of Adobe Photoshop continues to grow, even users with years of experience can feel overwhelmed by the many tools and methods for selecting or isolating parts of an image. Layers, channels, paths, clipping masks, layer masks, vector masks, the Pen tool, Magic Wand, and so on - all let users work on specific regions of an image, but in fundamentally different ways. Making clean, efficient selections are essential skills for any Photoshop user, whether a graphic designer, professional photographer, or hobbyist. Graphic designer, teacher, and Photoshop expert Nigel French saves you hours of frustration by illuminating the best selection tools and techniques for specific tasks, and the most flexible approaches to correcting and editing images in Photoshop. Using step-by-step examples, this book clarifies often-misunderstood selection methods, shows which masks best select a range of tone or color, and demonstrates how the right tools and techniques can help transform even the most mediocre picture into a polished image, saving you hours of time. - Learn the fundamentals of making selections, and when to choose which method - Blend images and replace backgrounds using layer, vector, and channel masks - Correct color and exposure using adjustment layers - Make next-to-impossible hair selections with channel masks - Create a non-destructive workflow, giving you total creative freedom.